Integrated Management of Mangrove Ecosystem Area in Geser Island and Surrounding Waters - Marasabessy, Jahdi; Abrahamsz, James; Sangadji, M. (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
This research was conducted from January to May 2024, with the aim of analyzing the potential and utilization of ecosystems in the waters of Geser Island and its surroundings, East Seram District, East Seram Regency, especially mangrove ecosystems. Primary and secondary data collection and analysis and processing of mangrove data and fish data to see the potential and level of utilization are expected to answer the objectives of this study. The results showed that the area of mangrove ecosystems in the study area reached 7.02 ha consisting of 5 species, with Rhizophora apiculata species having a high density for the category of trees, saplings and debris and Aegiceras corniculatum species in the category of trees and saplings are in a threatened position because they have a low percent cover. The results of the mangrove potential estimation, showed that the ratio of trees: saplings: mangrove saplings is 2 : 1 : 21, while the ratio of saplings: mangrove saplings reached 1 : 21. The ratio of trees and weeds is relatively small and can be called disproportionate, Potential fish resources are 47 species belonging to 34 genera and 26 families namely the Siganidae family (6 species), Lutjanidae family (4 species), Mugillidae family,Mullidae and Serranidae each with 3 species, Apogonidae, Carangidae, Gerridae, Labridae and Pomacentridae families each with 2 fish species.